Antioxidant and enzyme inhibitory properties of sacha inchi (Plukenetia volubilis) protein hydrolysate and its peptide fractions. Issue 12 (3rd October 2022) - Suwanangul, Saranya; Aluko, Rotimi E.; Sangsawad, Papungkorn; Kreungngernd, Danchai; Ruttarattanamongkol, Khanitta
Abstract: The objective of this study was to determine the in vitro activities such as antioxidant and inhibitions of angiotensin converting enzyme, dipeptidyl peptidase‐IV, prolyl oligopeptidase, and 3‐hydroxy‐3‐methyl‐glutaryl‐coenzyme A reductase of sacha inchi protein hydrolysate (SPH) and its membrane ultrafiltration peptide fractions. SPH was prepared after hydrolysis of sacha inchi protein using papain followed by separation into peptide fractions (F1: <1 kDa, F2: 1–3 kDa, F3: 3–5 kDa, and F4: 5–10 kDa) via ultrafiltration membranes. SPH and the peptide fractions were tested for multifunctional properties, specifically functional ability as antioxidants and enzyme inhibitors. Surface hydrophobicity was an important contributing factor to the activity of antioxidative peptides. The DPPH inhibitory activity of F4 was significantly higher ( p < .05) than activities of the SPH and other fractions. The smaller peptides with <1 kDa size (F1) showed the most potent ( p < .05) antioxidant properties based on the stronger scavenging of ABTS, DPPH, and superoxide radicals in addition to better attenuation of linoleic acid peroxidation. Moreover, the F1 was also the strongest inhibitor of angiotensin converting enzyme, dipeptidyl peptidase‐IV, prolyl oligopeptidase inhibition, and 3‐hydroxy‐3‐methyl‐glutaryl‐coenzyme A reductase based on the lower IC50 values. It was concluded that the smaller size of the F1 peptides was the main determinant of its strong antioxidant and enzyme inhibition potency, which could be taken as an advantage to formulate functional foods and nutraceuticals with potential activities in ameliorating some of the chronic human diseases. Practical applications: The results of present study indicate that SPH and its ultrafiltration fractions are potential sources of antihypertensive, antidiabetic, inhibition of POP, reduced cholesterol, and strong antioxidant peptides. The strong angiotensin converting enzyme, dipeptidyl peptidase‐IV, prolyl oligopeptidase inhibition, and 3‐hydroxy‐3‐methyl‐glutaryl‐coenzyme inhibitory efficiency of the F1 peptides (MW < 1 kDa) suggest potential utility as an antihypertensive, antidiabetic agent, reduce cholesterol and brain plasticity and memory formation because the small peptide size could enhance absorption from the gastrointestinal tract. Overall, results from this study indicate that SPH, especially the F1 peptides may have applications as ingredients for the formulation of functional foods and nutraceuticals. Abstract :